Brief Report - Monoclonal Antibodies Illustrate the Difficulties in Measuring Blocking TSH Receptor Antibodies - Davies, Terry F.; Morshed, Syed A.; Mezei, Mihaly; Latif, Rauf (Frontiers in Endocrinology, 2022)
TSH receptor (TSHR) antibodies are the cause of Graves’ disease and may also be found in patients with Hashimoto’s thyroiditis. They come in at least three varieties: thyroid stimulating, thyroid blocking and neutral. The measurement of TSH receptor antibodies in Graves’ disease and Hashimoto’s thyroiditis is a common clinical activity and can be useful in diagnosis and prognosis. We show that it is not possible to detect the blocking variety of TSHR antibody in patients with Graves’ disease because the stimulating antibody may overwhelm the measurement of blocking in the bioassays available for their measurement and may blind the valid interpretation of the results. To help explain this in more detail we show a series of studies with monoclonal TSHR antibodies which support this conclusion.